Disparities in inpatient treatment and expenditures among lung cancer patients under tiered social health insurance: a population-based study in China - Yaoyun Zhang; Yu He; Qing Wang; Ying Meng; Xinxin Xia; Xiaokang Ji; Qingbo Zhao; Yongchao Wang; Yifu Zhao; Chao Lv; Liming Zhu; Ding Wang; et al. (International Journal for Equity in Health)
Abstract Introduction Tiered social health insurance (SHI) schemes exist in many countries and may lead to significant disparities of healthcare and financial protection. The degree of cancer care inequalities under tiered SHI in China and other low- and middle-income countries (LMICs) remain poorly understood. Methods We obtained hospital discharged summary for 319,677 patients diagnosed with lung cancer between 2017 and 2021 in Shandong, China, and established propensity score-matched samples under the Urban and Rural Resident Basic Medical Insurance (URRBMI) and those under the Urban Employee Basic Medical Insurance (UEBMI). We ran multivariable regressions to assess the effects of SHI schemes on cancer treatment and expenditures. Subgroup analyses of cancer treatment were conducted based on whether the cancer had metastasized. Results In the matched samples, utilization of inpatient cancer care increased under both schemes from 2017 to 2021. Higher proportions of inpatient cancer care utilization were seen in those under UEBMI compared those under URRBMI, consistently with statistical significance. UEBMI was associated with a higher probability of receiving surgery in patients without metastasis, and higher probabilities of receiving radiotherapy or chemotherapy, targeted therapy, and immunotherapy in patients with metastasis. Patients under UEBMI were also less likely to be discharged against medical advice than those under URRBMI. Furthermore, UEBMI beneficiaries had 13.3% higher total expenditures but 19.1% lower out-of-pocket expenditures. Conclusions Significant gaps remained in access to inpatient treatment and financial protection for lung cancer, particularly in surgery for non-metastatic cancer. Targeted harmonization of benefit packages is needed to address pressing disparities in cancer care in LMICs with tiered SHI.